2022
DOI: 10.3389/fimmu.2022.877958
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Relevance of Anti-Hsp70 IgG Autoantibodies in Epidermolysis Bullosa Acquisita

Abstract: Stress-induced heat shock protein 70 (Hsp70) is a key intra- and extracellular molecular chaperone implicated in autoimmune processes. Highly immunogenic extracellular Hsp70 can activate innate and acquired (adaptive) immune responses driving the generation of anti-Hsp70 autoantibodies that are frequently observed in inflammatory/autoimmune disorders. We recently described the direct pathological role of extracellular Hsp70 in epidermolysis bullosa acquisita (EBA), an anti-type VII collagen autoantibody-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…The latter interactions may stimulate a humoral (auto)immune response and lead to the production of anti-Hsp (auto)antibodies. Although levels of anti-Hsp autoantibodies are elevated in patients suffering from numerous inflammatory and autoimmune diseases, including rheumatoid arthritis (RA) ( 37 40 ), juvenile idiopathic arthritis ( 41 ), autoimmune myasthenia gravis ( 42 ), dermatitis herpetiformis (DH) ( 43 ), psoriasis ( 44 ), systemic lupus erythematosus (SLE) ( 45 ), epidermolysis bullosa acquisita (EBA) ( 46 ), celiac disease (CD) ( 47 ), atopic dermatitis ( 48 ) and other (auto)inflammatory diseases, their pathological role is not fully understood ( Table 1 ). The mechanism of anti-Hsp antibody formation also remains to be clarified.…”
Section: Autoantibodies To Self-hsps In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The latter interactions may stimulate a humoral (auto)immune response and lead to the production of anti-Hsp (auto)antibodies. Although levels of anti-Hsp autoantibodies are elevated in patients suffering from numerous inflammatory and autoimmune diseases, including rheumatoid arthritis (RA) ( 37 40 ), juvenile idiopathic arthritis ( 41 ), autoimmune myasthenia gravis ( 42 ), dermatitis herpetiformis (DH) ( 43 ), psoriasis ( 44 ), systemic lupus erythematosus (SLE) ( 45 ), epidermolysis bullosa acquisita (EBA) ( 46 ), celiac disease (CD) ( 47 ), atopic dermatitis ( 48 ) and other (auto)inflammatory diseases, their pathological role is not fully understood ( Table 1 ). The mechanism of anti-Hsp antibody formation also remains to be clarified.…”
Section: Autoantibodies To Self-hsps In Health and Diseasementioning
confidence: 99%
“…Animals treated with Hsp70, or anti-Hsp70 IgG showed more intense clinical and histological disease activity. Mechanistically, anti-Hsp70 IgG enhanced neutrophil infiltration into the skin and activation of the NF-κB signaling pathway ( 22 , 46 , 59 ).…”
Section: Autoantibodies To Self-hsps In Health and Diseasementioning
confidence: 99%
“…Circulating anti-Hsp70 IgG autoantibodies were significantly elevated in EBA patients as compared to healthy individuals and positively correlated with IFN-γ in patients. The importance of these newly discovered, pathologically relevant autoantibodies has been proven in vivo, since anti-Hsp70 IgG-treated EBA mice had a more intense clinical and histological disease activity [ 52 ]. The above outcomes suggest that both autologous Hsp70 and autoantibodies to Hsp70 display proinflammatory activities in the context of EBA development [ 51 , 52 ].…”
Section: Hsp90 and Hsp70 As Potential Therapeutic Targets In Autoimmu...mentioning
confidence: 99%
“…Compared to Hsp90, the role of Hsp70 in AIBDs has been overall less studied ( 9 ). Two recent studies indicated that both extracellular Hsp70 and autoantibodies to Hsp70 display pro-inflammatory activities in the context of EBA development ( 16 , 17 ). In the first study, the in vivo pathophysiological relevance of extracellular Hsp70 was demonstrated in mice with experimental EBA in which elevated blood levels of this chaperone were recorded.…”
Section: Hsp90/70 and Aibdsmentioning
confidence: 99%
“…In addition, cell culture experiments using human naive peripheral blood mononuclear cells revealed that extracellular Hsp70 stimulated the secretion of the T-cell-derived pro-inflammatory cytokines IL-6 and IL-8 ( 16 ). In the second study, it was demonstrated that autoantibodies to Hsp70 may contribute to EBA development via enhanced neutrophil infiltration to the skin and activation of the NF-κB signalling pathway in an IFN-γ-associated manner ( 17 ).…”
Section: Hsp90/70 and Aibdsmentioning
confidence: 99%